2020
DOI: 10.1111/jocs.15057
|View full text |Cite
|
Sign up to set email alerts
|

Delayed disseminated intravascular coagulopathy post thoracic endovascular aortic repair (TEVAR)

Abstract: Disseminated intravascular coagulopathy (DIC) is a very rare outcome post endovascular repair of aortic aneurysm dissections. We present a case of a 70-year-old male who presented with DIC post a thoracic endovascular aortic repair (TEVAR) procedure due to a type 1A endoleak. Initially, the patient was treated with red blood cells and blood products; however, when failing to improve, he underwent a hybrid arch replacement. In this study, we will analyze the management of DIC post TEVAR and look at its presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…7-9 The first case of DIC after TEVAR was reported in 2014 in a small case series of Nienaber et al 6 Another 9 cases were reported until 2020. 10-19 In Table 3, patients’ age and gender, comorbidities, primary disease, initial intervention, and DIC time of diagnosis and clinical manifestations are reported.
Figure 3.Flow diagram depicting the selection process of the cases included in the review.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7-9 The first case of DIC after TEVAR was reported in 2014 in a small case series of Nienaber et al 6 Another 9 cases were reported until 2020. 10-19 In Table 3, patients’ age and gender, comorbidities, primary disease, initial intervention, and DIC time of diagnosis and clinical manifestations are reported.
Figure 3.Flow diagram depicting the selection process of the cases included in the review.
…”
Section: Resultsmentioning
confidence: 99%
“…In 2000, Cross et al described the first case of a female presenting with DIC following EVAR, 1 and another 16 cases have been published ever since. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] In the absence of robust data and pertinent guidelines, high uncertainty is present in the management of DIC post-EVAR. This review aimed to summarize the existing evidence, assist the decision-making process in clinical practice, and form a basis for further relevant research.…”
Section: Introductionmentioning
confidence: 99%